Predictors and outcomes of new-onset atrial fibrillation in patients with acute myocardial infarction - Vukmirović, Mihailo; Bošković, Aneta; Bukumirić, Zoran; Tomašević-Vukmirović, Irena; Vukmirović, Filip (Vojnosanitetski pregled, 2017)
Background/Aim. The onset of atrial fibrillation (AF) in the acute phase of myocardial infarction (MI) may be a predictor of poor prognosis. The aim of our study was to examine this relationship. Methods. Six hundred patients were enrolled in the study and divided into two groups. The first group included 48 patients with new-onset AF and the second group of 552 patients without this arrhythmia. Patients with previously registered AF were excluded from the study. We investigated the correlation between new-onset AF and intra-hospital mortality as well as mortality during the follow-up period of 48 months. We also analyzed predictors of this arrhythmia. Results. New-onset AF was registered in 48 (8%) patients. The independent predictors of this arrhythmia were older age, particularly more than 70 years [odds ratio 2.37; 95% confidence interval (CI) 1.23–4.58) and increased body mass index (odds ratio 1.17; 95% CI 1.04–1.33). Patients with new-onset AF had a higher mortality during the hospital course than patients without AF, but this difference was not statistically significant (10.4% vs 5.6%, p = 0.179). Patients with this arrhythmia had also a higher mortality after follow-up period of 48 months than patients without AF (33.3 % vs 17.8%, p = 0.009). Major adverse cardiac and cardiovascular events (MACCE) defined as death, recurrent MI, revascularization, and stroke were more after registered in patients with new-onset AF than in those with no this arrhythmia  after follow-up period of 48 months (52.1% vs 33.9%, p = 0.011). However, multivariate Cox's regression analysis demonstrated that new-onset AF was not an independent predictor of mortality during the follow-up period of 48 months (HR 0.68; 95% CI 0.38–1.20; p = 0.182). Conclusion. New-onset AF in patients with MI was associated with a higher mortality as well as MACCE after the follow-up period of 48 months but was not an independent predictor of mortality during this period.
Keywords: myocardial infarction; atrial fibrillation; risk factors; aged; obesity; prognosis; mortality; sensitivity and specificity